0445 A review of audiometric criteria for identifying noise-induced hearing loss among working adult populations. (21st August 2017) - Bogaert, Laura; Fan, Jonathan; Smith, Peter; Mustard, Cameron
Abstract : Objectives: Noise-induced hearing loss (NIHL) remains one of the most prevalent occupational diseases worldwide, despite widely adopted workplace hearing conservation efforts. There are no universally accepted criteria for NIHL, hampering epidemiologic comparisons. The primary objective of this review was to characterise audiometric criteria for NIHL in occupational health literature. Method: We searched Medline, Embase, Scopus, and ProQuest's Environmental Science and Pollution Management and Biological Sciences databases for primary studies published through to March 2017 that described NIHL in working adult populations using audiometric measures. Titles and abstracts were screened against eligibility criteria. From the eligible studies, we extracted NIHL definitions, country/region, population/setting, and study purpose (e.g., surveillance, compensation adjudication). Results: Our search resulted in 1303 unique citations. After title and abstract review 461 studies were deemed potentially relevant, including 137 published in languages other than English. A total of 129 English studies were eligible and included in the final synthesis. Generally, history of work-related noise exposure and either hearing loss at high frequencies or an audiometric notch at 4 kHz constituted NIHL in the included studies. However, the specific threshold in decibels for "hearing loss" and "notch" varied across studies, as did the range of sound frequencies used to calculate pure-tone averages to indicate NIHL. Conclusions: NIHL is a major global occupational health issue of our time. Our review of occupational literature highlights the variability in definitions of NIHL. Without a common definition of NIHL, comparisons between different populations will remain a challenge and inhibit progress in this area of research.